ANALYSIS OF TERM MEANING "COMPUTATIONAL THINKING" - LESSNER, Daniel (Journal of Technology and Information Education, 2014)
The article introduces the concept of computational thinking (CT). This ability "to think like a computer scientist while solving problems" draws more and more attention in relation to computer science education. We show and discuss a few definitions of CT. The concept can then be compared to key competences and literacies as used in Czechia.The second half of the article illustrates the theoretical specifications with a variety of examples from both everyday life and school education. Our "computer science" classes focus on ICT user skills. CT provides a convenient starting point for the quest for what is missing in our education.
Keywords: computer science education; computational thinking.